Low-silver conductive paste for low-temperature curing of HJT battery and preparation method of low-silver conductive paste
By using components such as micron-level silver-clad copper ball powder and sub-micron-scale ball silver powder, combined with epoxy resin and other materials, low-silver conductive paste is prepared, which solves the large amount and performance of silver powder of low-temperature cured HJT batteries in the prior art. The problem of insufficient results has achieved efficient and low-cost HJT battery production.
Patent Information
- Application Number
- CN202411400206.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art is difficult to develop a conductive paste with low silver content that can cure HJT batteries under low temperature conditions, and has good conductivity, printing and adhesion while reducing production costs.
Micron-level silver-clad copper ball powder and sub-micron-scale spherical silver powder are used as main components, combined with epoxy resin, curing agent, organic solvent and auxiliary agent, and through mechanical stirring and centrifugal dispersion, low-silver conductive paste is prepared. .
The conductive paste of the HJT battery cured under low temperature conditions of 150-200°C has been achieved, with good conductivity, printing and adhesion, which reduces the amount of silver powder, improves the photoelectric conversion efficiency, and reduces the production cost.
Smart Images

Figure BDA0005075053300000111 
Figure BDA0005075053300000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer-based electronic paste materials and HJT high-efficiency battery materials, and in particular to a low-silver-containing conductive paste for low-temperature curing HJT batteries and a preparation method thereof. Background Art
[0002] Although PERC cells are still the mainstream technology in the industry, their photoelectric conversion efficiency is close to the limit. N-type cells refer to solar cells that are formed by doping P elements into N-type semiconductor materials to form a P+ / N-type structure. They have the characteristics of high conversion efficiency, high bifaciality, low temperature coefficient, no light decay, good weak light effect, and longer carrier life. The main types of N-type cells are TOPCon, HJT and IBC, with theoretical maximum efficiencies of 28.7%, 29.2% and 29.1%, respectively, all higher than PERC's 24.5%. At present, the industry believes that the benefits of continuing to upgrade PERC cell technology are extremely low, and the market demand for PERC cells has been greatly reduced.
[0003] Among the three types of N-type cells mentioned above, HJT cells use low-cost amorphous silicon as the emission layer, and the entire process is completed at 200°C, with low energy consumption, avoiding the damage to silicon wafers caused by thermal stress generated by traditional battery processes at high temperatures, and becoming the research and development focus of the next generation of cells. In addition, it also has the characteristics of perfect passivation effect, high stability, and high electron mobility.
[0004] Because the HJT battery process has low temperature requirements, the high-temperature paste curing temperature of the traditional special glass as the bonding phase is above 800℃. Direct use will destroy the battery structure and seriously reduce the photoelectric conversion efficiency of the battery. Therefore, it is necessary to develop a low-temperature curing battery that is suitable for it. At present, the international market manufacturers that develop HJT pastes include Japan's Kyoto Electronics and the United States DuPont, and domestic paste companies such as Dico, Polymer and Jingyin, and each manufacturer is launching differentiated products.
[0005] In order to cope with the impact of international silver price fluctuations on the industry and reduce production costs, reducing the silver content in the slurry is an important direction for improvement. For example, CN116936159A provides a low-silver-content solar cell low-temperature sintering HJT silver paste and its preparation method. Although its silver content can be as low as 18.2%, it does not provide data such as the viscosity and stability of the slurry. Since the compatibility of silver-coated copper powder with solvents is poor, a large amount of solvent is required to make a slurry. Some solvents and curing agents will damage the structure of the silver-coated copper powder if they exceed a certain amount. The precipitated copper ions will accelerate the curing of the resin, causing the conductive slurry to completely deteriorate after 3 to 5 days and cannot be used any more. Therefore, so far, there has been no case of using only a single silver-copper powder in the low-silver slurry circulating in the market.
[0006] In addition, CN115376719A provides a low-temperature silver-coated copper paste for solar cells, wherein the conductive powder is composed of the following three types: silver-coated copper powder with a particle size of 1-5 microns, silver powder and / or silver-coated copper powder with a particle size of 500-800 nanometers, and silver powder with a particle size of 20-200 nanometers. The prepared paste has a silver content of 50%, but its volume resistivity is still too high, which has certain disadvantages in terms of photoelectric conversion efficiency. Summary of the invention
[0007] In view of the above problems existing in the prior art, the present invention provides a low-silver conductive paste for low-temperature curing HJT cells and a preparation method thereof. The HJT paste prepared by the present invention can be cured at a low temperature of 150-200°C, has good conductivity, printability and adhesion, and the silver content in the paste is only 30-50%, which greatly reduces the production cost of solar cells and effectively promotes the promotion of heterojunction solar cells.
[0008] The technical solution of the present invention is as follows:
[0009] A low-silver-containing conductive paste for low-temperature curing HJT cells, wherein the low-silver-containing conductive paste comprises the following components by weight percentage:
[0010] Micron-grade silver-coated copper ball powder 52-80%, submicron-grade spherical silver powder 14-42%, organic solvent 1-3%, curing agent 0.5%-2%, resin 2.5-4%, and auxiliary agent 0-1%.
[0011] Preferably, the micron-sized silver-coated copper ball powder is spherical with a median particle size of 4-6 μm; the submicron-sized spherical silver powder is spherical or flake-shaped, or a combination of spherical and flake-shaped; the submicron-sized spherical silver powder has a median particle size of 100-900 nm.
[0012] Furthermore, the micron-grade silver-coated copper ball powder has a D100 of 7-8 μm and a D10 of about 3 microns. In addition, it should be noted that the silver powder or silver-coated copper powder used in the present invention are mature commercial products on the market, not products in the research and development stage. It is worth noting that the resistance and density of the silver-coated copper ball shell powder are between those of silver powder and copper powder, and the resistance decreases with the increase of pressure. Although the electrical properties are excellent, it is easily oxidized at high temperatures, so it is only suitable for promotion and use in low-temperature slurries.
[0013] Furthermore, the silver content in the silver-coated copper powder is 10-30wt%, preferably 15-20wt%.
[0014] Preferably, the organic solvent comprises one or more of the following raw materials: terpineol, oleic acid, butyl carbitol, diethylene glycol monobutyl ether, diethylene glycol monoethyl ether acetate, and diethylene glycol monobutyl ether acetate.
[0015] Furthermore, the effect of the organic solvent is to disperse the silver-coated copper ball powder, silver powder, curing agent and additives, so that the slurry forms a fluid with good appearance and metallic color during the mechanical mixing process. The composition of multiple organic solvents can effectively regulate the viscosity and rheological properties of the slurry.
[0016] Preferably, the curing agent includes one or more of the following raw materials: polyamide, triethanolamine, sulfonyl dianiline, m-xylylenediamine, and 2-ethyl-4-methylimidazole.
[0017] Furthermore, the curing agent functions to cure the resin to form a cross-linked structure.
[0018] Preferably, the resin comprises one or more of the following raw materials: glycidyl ether epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin, alicyclic epoxy compound, acrylic resin.
[0019] More preferably, the glycidyl ether epoxy resin includes bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, hydrogenated bisphenol A epoxy resin or novolac epoxy resin; the glycidyl ester epoxy resin includes diglycidyl phthalate and hexahydrophthalate; the glycidyl amine epoxy resin includes triglycidyl-p-aminophenol and tetraglycidyl xylene diamine; the alicyclic epoxy compound includes bis(2,3-epoxycyclopentyl) ether, vinylcycloethylene diepoxide, and diisoprene diepoxide.
[0020] Furthermore, the resin acts as a binder in low-temperature silver paste, and can provide the paste with properties such as friction resistance and high conductivity.
[0021] Preferably, the auxiliary agent includes one or more of the following raw materials: silane coupling agent, fluorosilicone, hydrogenated castor oil, polyvinyl pyrrolidone, lactic acid monoglyceride, sodium dodecyl sulfate, fumed silica, polyamide wax, BYK11, BYK10, BYK354.
[0022] Furthermore, the auxiliary agents are of various types and can change the properties of the slurry.
[0023] The present invention also provides a method for preparing the low-silver-containing conductive paste, comprising the following steps:
[0024] (1) mixing the required percentages of resin, additives, and organic solvent, and obtaining a uniform and transparent organic system by centrifugal dispersion;
[0025] (2) adding a curing agent to the organic system obtained in step (1), mechanically stirring, or mixing evenly using a high-speed centrifuge to obtain an organic carrier;
[0026] (3) adding the micron-sized silver-coated copper ball powder and the submicron-sized spherical silver powder to the organic carrier three times, stirring evenly after each addition, stirring into a slurry after all the addition, and placing in a centrifuge for centrifugal dispersion and degassing;
[0027] (4) The slurry obtained in step 3 is ground and dispersed by a three-roll mill, and then collected. The collected slurry is centrifuged again, and the finished product of the low-silver-containing conductive slurry is obtained after degassing.
[0028] Preferably, the centrifuge speed in steps (1) and (2) is 1500 rpm, and the centrifugation time is 2 min; the centrifuge speed in steps (3) and (4) is 500 rpm, and the centrifugation time is 2 min.
[0029] Preferably, in step (4), the initial roll spacing and the final roll spacing of the three-roll mill are set to 90-30 μm, 60-20 μm, and 45-15 μm, and the rolling speed is less than 200 rpm.
[0030] Furthermore, in step (1), some insoluble resins or curing agents can be mixed with other diluents in proportion. If they are difficult to dissolve, they can be preheated, but the temperature does not exceed 70° C. to obtain a mixed solution.
[0031] Furthermore, in steps (3) and (4), it is necessary to avoid excessively high centrifugal speeds and excessively long centrifugal times after the addition of silver powder, which may cause the slurry to heat up and trigger a resin reaction.
[0032] The beneficial technical effects of the present invention are:
[0033] 1. The conductive paste provided by the present invention for use in heterojunction (HJT) solar cells has a wide curing temperature range (150-200°C), can maintain good printability, fluidity, and conductivity under low silver content, can be printed at a narrow line width of less than 12 microns, and has good printed grid line shape and strong adhesion.
[0034] In order to achieve this goal, the present invention firstly takes advantage of the excellent shrinkage, adhesion and processability of epoxy resin, and uses it as a base resin in combination with a suitable curing agent, so that the conductive silver paste can obtain excellent wear resistance and electrical properties; and the selected organic solvent has a reasonable evaporation temperature range, carries out less substances, and makes the grid line smooth.
[0035] In addition, the lattice of indium tin oxide (ITO) on the outer surface of the battery is a central cube with six oxygen atoms occupying the vertices and two oxygen atom vacancies. The sulfonyl group exists in sulfonyl dianiline, and the electron cloud of its oxygen atoms overlaps with ITO, causing the ITO lattice to be distorted. Some oxygen atoms fill the lattice vacancies to form new substances, which makes the gate wire and ITO more tightly bonded after the slurry is cured, improves the contact resistance of the slurry, greatly improves the adhesion of the gate wire, and improves the stability of the photovoltaic cell module.
[0036] 2. The present invention can solve the problem of high silver consumption in single-chip batteries in the current industry. The industry solution to this problem is to improve the existing printing technology, that is, to develop a paste that can be printed under a narrower line width opening screen, and to apply low-temperature pure silver paste (front printing) and low-temperature silver-copper paste (back printing) at the same time, or to select low-temperature silver-copper paste for both sides.
[0037] The present invention uses a variety of additives, curing agents and a variety of resins to form a dense cross-linked network structure after curing, which can effectively shrink the distance between conductive phases and form an electron flow path, thereby reducing the line resistance of the battery grid formed by the metallized battery cell of the conductive paste. This allows the present invention to use a large amount of silver-coated copper spherical shell powder in the paste, greatly reducing the amount of silver powder, and can also produce excellent ohmic contact performance when used in HJT solar cells, with excellent photoelectric conversion efficiency.
[0038] 3. The present invention solves the problem of large slurry fineness. Since the silver-coated copper spherical shell powder has a large particle size and poor surface wettability, the powder is difficult to disperse in an organic solvent, but tends to form larger particles and coat the organic carrier in the particles. Such large particles are easily crushed into flake powder in the subsequent grinding process, destroying the powder structure and weakening the electrical properties and printability of the slurry. Choosing an unsuitable solvent will make it difficult to grind the slurry using a three-roll mill, forming flaky powder visible to the naked eye. Although these large-particle powders can be filtered and removed, the fineness of the slurry will become larger and it will be difficult to print with a narrow line width screen.
[0039] The present invention, by using non-ionic dispersant BYK111, wets the surface of the silver-coated copper powder, which helps the organic carrier form a short and thick liquid bridge between the powders, and can effectively avoid such a situation. At the same time, due to the use of a variety of curing agents, such as the combination of imidazole catalysts and isocyanate curing agents, more heat is released during curing, and this heat can melt the surface of the nano silver powder with a larger surface energy, and combine with other powders, so that the conductive phase formed has more point contacts, or even surface contacts.
[0040] 4. The present invention ensures that the slurry has high reliability. After the conductive slurry is printed, the narrow and high grid lines are formed, which helps to improve the short-circuit current (ISC) of the battery cell, which is extremely important for improving the photoelectric conversion efficiency of the battery; some solvents with good dispersibility may react with the silver-coated copper shell powder, causing copper ions to overflow, causing the epoxy resin to cure prematurely, and making it difficult to use later. The present invention selects a more suitable silver powder. Due to its large volume and mass, it effectively reduces the migration of substances during the curing process, making the line shape more neat.
[0041] 5. In general, the paste of the present invention does not require high-temperature sintering, has a simple method of use, greatly reduces the cost of raw materials, and has low body resistance, line resistance and contact resistance. Its photoelectric conversion capability is comparable to that of pure silver paste, which is conducive to the promotion of HJT technology in the market and has broad application prospects and market value. DETAILED DESCRIPTION
[0042] The present invention is described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] Embodiment 1:
[0044] This embodiment prepares a low-silver-containing conductive paste for low-temperature curing HJT batteries, and the preparation method is as follows:
[0045] (1) 2% of bisphenol A epoxy resin, 0.3% of diisoprene diepoxide, 0.3% of diglycidyl phthalate, 1% of oleic acid, 2% of terpineol, 0.1% of BYK111 and 0.2% of hydrogenated castor oil were mixed and dispersed at high speed using a centrifuge to prepare a uniform transparent organic system, which accounted for 5.9% of the total mass.
[0046] (2) 0.3% sulfonyl dianiline and 0.3% 2-ethyl-4-methylimidazole were added to the above organic system, and the mixture was centrifuged at high speed to obtain an organic carrier, which accounted for 6.5% of the total mass.
[0047] (3) adding 54.5% of silver copper powder (with a median particle size of 5 μm and a spherical shape) with a silver coating amount of 20% and 39% of pure silver ball powder with a particle size of about 300 nm to the organic carrier in three times, stirring evenly after each addition until all the powder is added and stirred into a slurry, and then centrifuged and dispersed in a centrifuge for degassing;
[0048] (4) The prefabricated slurry is ground using a three-roll mill, and then dispersed and degassed using a centrifuge to obtain a finished slurry. The silver content of the slurry prepared in this embodiment is 50%.
[0049] Embodiment 2:
[0050] This embodiment prepares a low-silver-containing conductive paste for low-temperature curing HJT batteries, and the preparation method is as follows:
[0051] (1) 2% of bisphenol A epoxy resin, 0.3% of diisoprene diepoxide, 0.3% of diglycidyl phthalate, 1% of oleic acid, 2% of terpineol, 0.1% of BYK111 and 0.2% of hydrogenated castor oil were mixed and dispersed at high speed using a centrifuge to prepare a uniform transparent organic system, which accounted for 5.9% of the total mass.
[0052] (2) 0.3% sulfonyl dianiline and 0.3% 2-ethyl-4-methylimidazole were added to the above organic system, and the mixture was centrifuged at high speed to obtain an organic carrier, which accounted for 6.5% of the total mass.
[0053] (3) adding 67% of silver copper powder (with a median particle size of 5 μm and a spherical shape) with a silver coating amount of 20% and 26.5% of pure silver ball powder with a particle size of about 300 nm to the organic carrier in three times, stirring evenly after each addition until all the mixture is added and stirred into a slurry, and then centrifuged and dispersed in a centrifuge for degassing;
[0054] (4) The prefabricated slurry is ground using a three-roll mill, and then dispersed and degassed using a centrifuge to obtain a finished slurry. The silver content of the slurry prepared in this embodiment is 40%.
[0055] Embodiment 3:
[0056] This embodiment prepares a low-silver-containing conductive paste for low-temperature curing HJT batteries, and the preparation method is as follows:
[0057] (1) 2.3% of bisphenol A epoxy resin, 0.3% of diisoprene diepoxide, 0.3% of diglycidyl phthalate, 0.5% of oleic acid, 1.5% of terpineol, and 0.5% of diethylene glycol monobutyl ether are dispersed at high speed using a centrifuge to prepare a uniform transparent organic system, which accounts for 5.4% of the total mass.
[0058] (2) 0.45% of sulfonyl dianiline and 0.15% of 2-ethyl-4-methylimidazole were added to the above organic system, and the mixture was centrifuged at high speed to obtain an organic carrier, which accounted for 6% of the total mass.
[0059] (3) adding 74% of silver-coated silver copper powder (with a median particle size of 5 μm and a spherical shape) with a silver coating amount of 20% and 20% of pure silver ball powder with a particle size of about 300 nm to the organic carrier in three times, stirring evenly after each addition until all the mixture is added and stirred into a slurry, and then centrifuged and dispersed in a centrifuge for degassing;
[0060] (4) The prefabricated slurry is ground using a three-roll mill, and then dispersed and degassed using a centrifuge to obtain a finished slurry. The silver content of the slurry prepared in this embodiment is about 35%.
[0061] Embodiment 4:
[0062] This embodiment prepares a low-silver-containing conductive paste for low-temperature curing HJT batteries, and the preparation method is as follows:
[0063] (1) 2.2% of bisphenol A epoxy resin, 0.35% of bis(2,3-epoxycyclopentyl) ether, 1% of butyl carbitol, 2% of terpineol and 0.2% of silane coupling agent were mixed and dispersed at high speed using a centrifuge to prepare a uniform transparent organic system, which accounted for 5.75% of the total mass.
[0064] (2) 0.15% sulfonyl dianiline and 0.6% 2-ethyl-4-methylimidazole were added to the above organic system, and the mixture was centrifuged at high speed to obtain an organic carrier, which accounted for 6.5% of the total mass.
[0065] (3) adding 74.7% of silver copper powder (with a median particle size of 5 μm and a spherical shape) with a silver coating amount of 15% and 18.8% of pure silver ball powder with a particle size of about 300 nm to the above organic carrier in three times, stirring evenly after each addition until all the mixture is added and stirred into a slurry, and then centrifuged and dispersed in a centrifuge for degassing;
[0066] (4) The prefabricated slurry is ground using a three-roll mill, and then dispersed and degassed using a centrifuge to obtain a finished slurry. The silver content of the slurry prepared in this embodiment is 30%.
[0067] Embodiment 5:
[0068] This embodiment prepares a low-silver-containing conductive paste for low-temperature curing HJT batteries, and the preparation method is as follows:
[0069] (1) 1.5% of hydrogenated bisphenol A epoxy resin, 0.5% of phenolic epoxy resin, 0.2% of diglycidyl phthalate, 0.3% of diisoprene diepoxide, 0.3% of oleic acid, 0.8% of diethylene glycol monoethyl ether acetate, 1.6% of pine alcohol, and 0.3% of silane coupling agent are mixed and dispersed at high speed using a centrifuge to prepare a uniform transparent organic system, which accounts for 5.5% of the total mass.
[0070] (2) 0.2% sulfonyl dianiline and 0.8% polyamide were added to the above organic system, and centrifuged at high speed using a centrifuge to obtain an organic carrier, which accounted for 6.5% of the total mass.
[0071] (3) adding 54.5% of silver copper powder (with a median particle size of 5 μm and a spherical shape) with a silver coating amount of 20%, 26% of pure silver ball powder with a particle size of about 300 nm, and 13% of pure silver ball powder with a particle size of about 900 nm to the above organic carrier in three portions, stirring evenly after each addition until all the powder is added and stirred into a slurry, and then centrifuged and dispersed in a centrifuge for degassing;
[0072] (4) The prefabricated slurry is ground using a three-roll mill, and then dispersed and degassed using a centrifuge to obtain a finished slurry. The silver content of the slurry prepared in this embodiment is 50%.
[0073] Embodiment 6:
[0074] This embodiment prepares a low-silver-containing conductive paste for low-temperature curing HJT batteries, and the preparation method is as follows:
[0075] (1) 1.8% of bisphenol F epoxy resin, 0.5% of acrylic resin, 0.4% of tetraglycidyl xylene diamine, 2% of pineol, 0.7% of diethylene glycol monobutyl ether acetate, 0.1% of polyvinyl pyrrolidone, and 0.1% of polyamide wax are mixed and dispersed at high speed using a centrifuge to prepare a uniform transparent organic system, which accounts for 5.6% of the total mass.
[0076] (2) 0.4% m-xylylenediamine and 0.5% triethanolamine are added to the above organic system, and the mixture is centrifuged at high speed to obtain an organic carrier, which accounts for 6.5% of the total mass.
[0077] (3) adding 54.5% of silver-copper powder (with a median particle size of 5 μm and a spherical shape) with a silver coating amount of 20%, 20% of pure silver ball powder with a particle size of about 300 nm, and 19% of pure silver ball powder with a particle size of about 900 nm to the above organic carrier, adding the powder to the organic carrier in three times, stirring evenly after each addition, until all the powder is added and stirred into a slurry, and then placing the powder in a centrifuge for centrifugal dispersion and degassing;
[0078] (4) The prefabricated slurry is ground using a three-roll mill, and then dispersed and degassed using a centrifuge to obtain a finished slurry. The silver content of the slurry prepared in this embodiment is 50%.
[0079] Comparative Example 1:
[0080] In this comparative example, a low-silver-containing conductive paste for low-temperature curing HJT cells is prepared, and the preparation method is as follows:
[0081] (1) 2% of bisphenol A epoxy resin, 0.3% of diisoprene diepoxide, 0.3% of diglycidyl phthalate, 1% of oleic acid, 2% of terpineol, 0.1% of BYK11 and 0.2% of hydrogenated castor oil were mixed and dispersed at high speed using a centrifuge to prepare a uniform transparent organic system, which accounted for 5.9% of the total mass.
[0082] (2) 0.3% sulfonyl dianiline and 0.3% 2-ethyl-4-methylimidazole were added to the above organic system, and the mixture was centrifuged at high speed to obtain an organic carrier, which accounted for 6.5% of the total mass.
[0083] (3) adding 75% of pure silver flake powder with a particle size of about 2 microns and 18.5% of pure silver ball powder with a particle size of about 300 nm to the organic carrier in three times, stirring evenly after each addition until all the powder is added and stirred into a slurry, and then centrifuged and dispersed in a centrifuge for degassing;
[0084] (4) The prefabricated slurry is ground using a three-roll mill, and then dispersed and degassed using a centrifuge to obtain a finished conductive slurry.
[0085] The preparation process parameters of the above-mentioned Examples 1-6 and Comparative Example 1 are: the centrifuge speed in steps (1) and (2) is 1500 rpm, and the centrifuge time is 2 min; the centrifuge speed in steps (3) and (4) is 500 rpm, and the centrifuge time is 2 min. In step (4), the initial roll spacing and the final roll spacing of the three-roll mill are set to 90-30 μm, 60-20 μm, and 45-15 μm, and the roller speed is less than 200 rpm.
[0086] Comparative Example 2:
[0087] The slurry was prepared by the method described in Example 4 of CN113707363A "A low-temperature curing conductive silver paste with high tensile strength and high conductivity and its preparation method".
[0088] Test example:
[0089] The conductive pastes prepared in the above examples and comparative examples were subjected to performance tests, and the test method was as follows:
[0090] (1) Volume resistance: Using silicon cell as substrate, manually print a rectangular pattern with a width of 5 mm and a length greater than 5 cm, and then cure it in an oven at 200°C for 7 min. The resistance and film thickness of the obtained sample were tested by a multimeter and a step profiler, and the volume resistance was obtained by substituting them into the formula.
[0091] (2) Photoelectric conversion efficiency: A screen printer was used with an opening of 18 μm on the front secondary grid plate, a printing speed of 300 m / s, and an ink return speed of 1000 mm / s. The conductive paste was printed on the silicon wafer and then cured at 200°C for 7 min in a chain sintering furnace. The cured samples were then tested for electrical properties by an IV tester (HSC1-1S, Shanghai Heshuang Solar Technology Co., Ltd.).
[0092] (3) Printing performance test: Use an EL tester to observe whether there is any broken grid on the screen after printing.
[0093] (4) Viscosity: The viscosity of the sample at 25°C was tested using a viscometer with a rotor of SC4-14, and the viscosity value was recorded when the rotor rotated at a speed of 10 rpm for 30 s.
[0094] (5) Adhesion test: Use 3M adhesive tape to adhere to the cured test pattern (cell for IV test), stick a piece of tape vertically, and use a high-grade drawing eraser to rub it flat. After leaving it for 1 minute, pull off the tape vertically and quickly (10cm / s) to observe whether the grid line of the cell falls off.
[0095] The test results of the above embodiments and comparative examples are shown in Table 1.
[0096] Table 1 Test results of Examples 1-6 and Comparative Examples 1-2
[0097]
[0098]
[0099] From the above data, it can be seen that the organic carrier designed by the present invention can be used with different silver content gradients to prepare conductive paste after slight modification. Compared with the pure silver paste in Comparative Example 1, the volume resistivity of Examples 1-4 is slightly increased, and the photoelectric conversion efficiency is close, which meets the market's goal of increasing efficiency and can be selected by the market. Comparative Example 2 uses silver powders of different particle sizes and shapes. Although the volume resistivity and photoelectric conversion efficiency meet the standards, compared with the silver-coated copper paste proposed in this patent, the cost is high and it is currently not competitive in the market.
[0100] It should be pointed out that there is a slight difference between the silver paste performance of the above-mentioned comparative example 2 and the silver paste performance of Example 4 of CN113707363A. This is due to the different manufacturers of the raw silver powder, but in general the difference is not significant.
[0101] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and implementation modes, and can be fully applicable to various fields suitable for the present invention. For those familiar with the art, for those of ordinary skill in the art, various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principle and spirit of the present invention. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A low-silver conductive paste for low-temperature curing HJT cells, characterized in that: The low silver-containing conductive paste is composed of the following components by weight percentage: Micron-grade silver-coated copper ball powder 52-80%, submicron-grade spherical silver powder 14-42%, organic solvent 1-3%, curing agent 0.5%-2%, resin 2.5-4%, and auxiliary agent 0-1%.
2. The low silver-containing conductive paste according to claim 1, characterized in that: The micron-level silver-coated copper ball powder is spherical, and the median particle size is 4-6 μm; the submicron-level spherical silver powder is spherical or flake-shaped, or a combination of spherical and flake-shaped; the median particle size of the submicron-level spherical silver powder is 100-900 nm.
3. The low silver-containing conductive paste according to claim 1, characterized in that: The organic solvent includes one or more of the following raw materials: pinene alcohol, oleic acid, butyl carbitol, diethylene glycol monobutyl ether, diethylene glycol monoethyl ether acetate, and diethylene glycol monobutyl ether acetate.
4. The low silver-containing conductive paste according to claim 1, characterized in that: The curing agent includes one or more of the following raw materials: polyamide, triethanolamine, sulfonyl dianiline, meta-xylylenediamine, and 2-ethyl-4-methylimidazole.
5. The low silver-containing conductive paste according to claim 1, characterized in that: The resin comprises one or more of the following raw materials: glycidyl ether epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin, alicyclic epoxy compound, acrylic resin.
6. The low silver-containing conductive paste according to claim 1, characterized in that: The glycidyl ether epoxy resin includes bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, hydrogenated bisphenol A epoxy resin or novolac epoxy resin; the glycidyl ester epoxy resin includes diglycidyl phthalate and hexahydrophthalate; the glycidyl amine epoxy resin includes triglycidyl-p-aminophenol and tetraglycidyl xylene diamine; the alicyclic epoxy compound includes bis(2,3-epoxycyclopentyl) ether, vinyl cycloethylene diepoxide, and diisoprene diepoxide.
7. The low silver-containing conductive paste according to claim 1, characterized in that: The auxiliary agent includes one or more of the following raw materials: silane coupling agent, fluorosilicone, hydrogenated castor oil, polyvinyl pyrrolidone, lactic acid monoglyceride, sodium dodecyl sulfate, fumed silica, polyamide wax, BYK11, BYK10, BYK354.
8. The method for preparing the low-silver-containing conductive paste according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) mixing the required percentages of resin, additives, and organic solvent, and obtaining a uniform and transparent organic system by centrifugal dispersion; (2) adding a curing agent to the organic system obtained in step (1), mechanically stirring, or mixing evenly using a high-speed centrifuge to obtain an organic carrier; (3) adding the micron-sized silver-coated copper ball powder and the submicron-sized spherical silver powder to the organic carrier three times, stirring evenly after each addition, stirring into a slurry after all the addition, and placing in a centrifuge for centrifugal dispersion and degassing; (4) The slurry obtained in step 3 is ground and dispersed by a three-roll mill, and then collected. The collected slurry is centrifuged again, and the finished product of the low-silver-containing conductive slurry is obtained after degassing.
9. The preparation method according to claim 8, characterized in that: In steps (1) and (2), the centrifuge speed is 1500 rpm and the centrifugation time is 2 min respectively; in steps (3) and (4), the centrifuge speed is 500 rpm and the centrifugation time is 2 min respectively.
10. The preparation method according to claim 9, characterized in that: In step (4), the initial roll spacing and the final roll spacing of the three-roll mill are set to 90-30 μm, 60-20 μm, and 45-15 μm, and the rolling speed is less than 200 rpm.
Citation Information
Patent Citations
Low-temperature curing conductive silver paste with high tensile force and high conductivity and preparation method of low-temperature curing conductive silver paste
CN113707363A
Low-silver-content low-temperature sintering type HJT silver paste for solar cell and preparation method of low-silver-content low-temperature sintering type HJT silver paste
CN116936159A
Cited By
Conductive slurry for base metal layer of stacked gate of BC battery and preparation method of conductive slurry
CN119673527A
Conductive slurry, electrode, preparation method and photovoltaic cell
CN121545816A